Transmission Strategies for Wireless Relay Networks Obtained from Linear Finite-Field Deterministic Models - Schrammar, Nicolas; Skoglund, Mikael (IEEE transactions on communications, 2012)
In this paper we show how the recently proposed linear finite-field deterministic model (LFFM) can be used to design transmission strategies for the corresponding AWGN model of wireless relay networks. The transmission scheme in the AWGN model uses hierarchical modulation to transmit information on multiple layers. We show that a transmission strategy in the LFFM can be translated to the AWGN model if it is coordinated, that is, if the amount of interference is limited in a certain way. We consider two types of coordination, full and partial, with different restrictions on the transmission scheme. In both cases we show that the rate in the AWGN model is at most a constant gap below the rate in the LFFM, which provides a link between the models. Closed-form upper bounds on the gap are derived based on the analysis of noise and interference forwarding. The bounds are evaluated numerically, and the dependency on the system parameters and the parameters of coordination are discussed. The trade-off between full and partial coordination and the corresponding parameters are illustrated.